Makna Lotus dalam Lagu LiSA - GURENGE - Nabila, Alya Husna; Puspitasari, Diana; Kadafi, Muammar (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 1 (2024)DO - 10.24843/JS.2024.v06.i01.p01, 2024)
This research contains the meaning of lotus in the song LiSA - Gurenge which has an implied meaning regarding the philosophical value of lotus which is analogous to the stages of human life. The purpose of this study is to describe the representation of the lotus flower and its meaning in the Gurenge song for Japanese society. This study uses a qualitative descriptive method, see note, then the theoretical concept used in this research is the semiotic theory of Charles Sanders Peirce. The results of this study found that there is a representation of the living teaching of the Lotus Sutra which is believed by Tiantai and Nichiren Buddhists who are widespread in East Asia. Based on the results of the research, it can be concluded that the Gurenge song describes the human process in an effort to achieve the highest enlightenment to reach nirvana in accordance with Buddhist teachings